2013
DOI: 10.1073/pnas.1320383110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cancer initiating cells in K-Ras driven lung adenocarcinoma

Abstract: Ubiquitous expression of a resident K-RasG12V oncogene in adult mice revealed that most tissues are resistant to K-Ras oncogenic signals. Indeed, K-RasG12V expression only induced overt tumors in lungs. To identify these transformation-permissive cells, we induced K-RasG12V expression in a very limited number of adult lung cells (0.2%) and monitored their fate by X-Gal staining, a surrogate marker coexpressed with the K-RasG12V oncoprotein. Four weeks later, 30% of these cells had proliferated to form small cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
156
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(172 citation statements)
references
References 19 publications
15
156
1
Order By: Relevance
“…32 Later studies in mice with activated K-ras in SP-C + or CC10 + cells using conditional Cre ER knock-in alleles indicated that tumors arose only in the alveoli, although recombination occurred throughout the bronchioles, the BADJ and the bronchioalveolar stem cells, which are CC10/SP-C double-positive cells. 21,31 We found that KLF4 deletion increased the number of AT2 cells and enhanced K-ras-mediated lung tumorigenesis (Figures 2e-g and 4), consistent with the findings that AT2 cells are the major origin of lung cancer 22 and that K-ras regulates self-renewal of AT2 cells. 21 Compared with lesions at 8 weeks post infection, more adenomas and adenocarcinomas arose at 16 weeks in K-ras LSL-G12D/+ ;Klf4 fl/fl mice, whereas only trace amount of Figure 7a).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…32 Later studies in mice with activated K-ras in SP-C + or CC10 + cells using conditional Cre ER knock-in alleles indicated that tumors arose only in the alveoli, although recombination occurred throughout the bronchioles, the BADJ and the bronchioalveolar stem cells, which are CC10/SP-C double-positive cells. 21,31 We found that KLF4 deletion increased the number of AT2 cells and enhanced K-ras-mediated lung tumorigenesis (Figures 2e-g and 4), consistent with the findings that AT2 cells are the major origin of lung cancer 22 and that K-ras regulates self-renewal of AT2 cells. 21 Compared with lesions at 8 weeks post infection, more adenomas and adenocarcinomas arose at 16 weeks in K-ras LSL-G12D/+ ;Klf4 fl/fl mice, whereas only trace amount of Figure 7a).…”
Section: Discussionsupporting
confidence: 88%
“…To test the effect of Klf4 deletion on other cell types, we stained the lung tissues with antibodies to AT1 cell marker reported that AT2 cells are the predominant cells of origin of adenocarcinoma that is driven by K-ras activation. [21][22][23]31,34 Our results suggest that Klf4 deletion could be a driving force of lung tumorigenesis through stimulating AT2 cells in mouse lung.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…They also give rise to lung adenocarcinoma induced by oncogenic Kras (1,(3)(4)(5). AT2 cells are derived from bipotent progenitor cells at the sacculation stage (1).…”
mentioning
confidence: 99%
“…However, in more recent studies that targeted the expression of oncogenic Kras G12D only in cells expressing club cell secretory protein (CCSP), such as club cells and BASCs, or only in cells expressing surfactant protein C (SPC), such as AT2 cells and BASCs, AT2 cells seemed to be the only cells that were capable of giving rise to advanced ADC in the alveolar space, whereas club cells and BASCs seemed to be limited to driving bronchiolar hyperplasia within the same time frame 59 . Using these approaches, it is notable that changes in the cells of origin were evident when the genotype for tumour initiation was altered (for example, to include p53 loss) or if injury or inflammation were present during tumour initiation (for example, after adenovirus infection or after naphthalene-induced injury) 56,[59][60][61][62][63] . Injury or inflammation probably more closely mimics the scenario of tumour initiation in humans, in which environmental influences and ongoing injury occur in contrast to the relatively sterile mouse colony.…”
Section: Cell(s) Of Origin For Nsclc Heterogeneity At Tumour Initiationmentioning
confidence: 99%